Human telomeres that carry an integrated copy of human herpesvirus 6 are often short and unstable, facilitating release of the viral genome from the chromosome. Issue 1 (19th September 2013) - Huang, Yan; Hidalgo-Bravo, Alberto; Zhang, Enjie; Cotton, Victoria E.; Mendez-Bermudez, Aaron; Wig, Gunjan; Medina-Calzada, Zahara; Neumann, Rita; Jeffreys, Alec J.; Winney, Bruce; Wilson, James F.; Clark, Duncan A.; et al.
Abstract: Linear chromosomes are stabilized by telomeres, but the presence of short dysfunctional telomeres triggers cellular senescence in human somatic tissues, thus contributing to ageing. Approximately 1% of the population inherits a chromosomally integrated copy of human herpesvirus 6 (CI-HHV-6), but the consequences of integration for the virus and for the telomere with the insertion are unknown. Here we show that the telomere on the distal end of the integrated virus is frequently the shortest measured in somatic cells but not the germline. The telomere carrying the CI-HHV-6 is also prone to truncations that result in the formation of a short telomere at a novel location within the viral genome. We detected extra-chromosomal circular HHV-6 molecules, some surprisingly comprising the entire viral genome with a single fully reconstituted direct repeat region (DR) with both terminal cleavage and packaging elements (PAC1 and PAC2). Truncated CI-HHV-6 and extra-chromosomal circular molecules are likely reciprocal products that arise through excision of a telomere-loop (t-loop) formed within the CI-HHV-6 genome. In summary, we show that the CI-HHV-6 genome disrupts stability of the associated telomere and this facilitates the release of viral sequences as circular molecules, some of which have the potential to become fully functioning viruses.